Effects of two training devices on the activity of eleven shoulder muscles during Azarian in gymnastics - Bernasconi, S.; Tordi, N.; Parratte, B.; Roullion, J.-D.; Monnier, G. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Difficult elements of strength are presented during a rings movement in the Men`s Artistic Gymnastic. Azarian is a difficult strength element composed by a backward rotation of 360° from a hanging to a support position in the sagital plane, followed by a static strength element, the Iron Cross (IC). During the whole movement, the gymnast must keep his arm straight, his shoulders under the top of the rings and maintains the IC for two seconds. Two training devices could be used to reproduce the Azarian movement: the Belt and the Herdos (Fig. 1). Both reduce the shoulder joint torque during the performance of Azarian, but no information on the muscle activity is available for an objective utilisation. The purpose of our study was therefore to use surface electromyography to compare the effects of these two training devices on the activity and coordination of eleven shoulder muscle during the performance of Azarian. Methods Seven male gymnasts have used the Herdos and the Belt to perform an Azarian. During each trial, separated by 2 minutes at rest, a group of four shoulder muscles was studied. This procedure was reproduced twice to study two other groups of four muscles. The three trials were separated by 10-min at rest. The muscles groups were: 1) the latissimus dorsi, serratus anterior, rhomboideus and pectoralis major muscles; 2) the supraspinatus, deltoideus (acromial part), biceps brachii and triceps brachii (long head) muscles; 3) the deltoideus (clavicular and scapular parts), latissimus dorsi and infraspinatus muscles. RMS and a parameter called `muscle part` were calculated to investigate the muscle activity and coordination in the three muscles groups. The `muscle part` represents the contribution of each muscle in its group. A two-way (device vs. time) ANOVA design on ranks with repeated measurements was performed for RMS and `muscle part`. Multiple comparisons were performed using Tukey post hoc test and significance was set at P<0.01. Results A main effect between the two devices (Fig. 2) was observed for RMS of the muscle biceps brachii and for `muscle parts` of muscles biceps brachii and deltoideus, acromial part. Significant interactions were also observed for RMS of muscles deltoideus (clavicular, acromial and scapular parts), and for `muscle parts` of muscles serratus anterior and supraspinatus (results not presented). Discussion/Conclusion RMS results show that the muscle biceps brachii is more active when the gymnast is using the Belt than the Herdos: it more stabilises the elbow joint with the Belt. Results for the `muscle part` signify that the Belt requires a higher contribution of the muscle biceps brachii to stabilise the shoulder joint, whereas the muscle deltoideus, acromial part, has a more important stabilisation action with the Herdos. Significant interactions show that each device modifies differently the activity of the three parts of the muscle deltoideus and the muscle part of the muscles serratus anterior and supraspinatus during the movement. The choice of one device must therefore be done in accordance to muscle training objectives.